Constitutional law for criminal justice - Kanovitz, Jacqueline R. (Routledge Taylor & Francis Group, 2024)
"Constitutional Law for Criminal Justice, 16th Edition, offers criminal justice professionals the training they need to recognize the constitutional principles that apply to their daily work. Kanovitz and revision authors Jefferson Ingram and Christopher Devine provide a comprehensive, well-organized, and up-to-date analysis of constitutional issues that affect the US justice system. Chapter 1 summarizes the organization and content of the Constitution, the Bill of Rights, and the Fourteenth Amendment. The next eight chapters cover the constitutional principles that regulate investigatory detentions, traffic stops, arrests, use of force, search and seizure, technologically assisted surveillance, the Wiretap Act, interrogations and confessions, self-incrimination, witness identification procedures, the right to counsel, procedural safeguards during criminal trials, First Amendment issues relevant to law enforcement, and capital punishment. The final chapter covers the constitutional rights of criminal justice professionals in the workplace, their protection under Title VII of the Civil Rights Act, and their accountability under 42 U.S.C. 1983 for violating the constitutional rights of others. Part II contains abstracts of key judicial decisions exemplifying how the doctrines covered in earlier chapters are being applied by the courts. The combination of text and cases creates flexibility in structuring class time. This book makes complex concepts accessible to students in all levels of criminal justice education. The chapters begin with an outline and end with a summary. Key Terms and Concepts are defined in the Glossary. Tables, figures, and charts are used to synthesize and simplify information. The result is an incomparably clear, student-friendly textbook that has remained a leader in criminal justice education for more than 50 years"--